Stereotypes of Chinese culture in American picture books through written and visual languages - Wangbei Tu; Kavitha Ganesan; Rose Patsy Tibok (Pusat Penataran IImu dan Bahasa, 2021)
Language is a communication system which consists of a set of sounds or written symbols. As a specific form of children's book, picture books combine pictures and words to tell a complete story, pictures in which can be accepted as visual language because meaning can be conveyed from one party to another. Language is also the carrier of culture. Apart from the explicit meaning of the story, there are limitations in cultural connotations implied in the picture-word language system. Chinese culture is a very important part of the multiculturalism in American picture books. Through this study, it has been found that there are some stereotypes in the display of Chinese culture in American picture books. Firstly, the full view of Chinese culture is overshadowed by the excessive attention and localization of cultural symbols such as the Chinese dragon and the Spring Festival. Secondly, the confusion of Asian cultures in visual language and written language weakens the uniqueness of Chinese culture. Thirdly, Information disorder weakens the authenticity of Chinese culture. The reasons of these stereotypes are rooted in the real attitude of the multiculturalism in America. The misinterpretation results in the following complications: (i) Chinese culture is equated with the culture of Chinese Americans; (ii) Chinese culture is regarded as static, which leads to serious homogenization; (iii)The sightseeing attitude towards Chinese culture resulted in the overfocus of cultural symbols.